Development of food‐grade expression system for d‐allulose 3‐epimerase preparation with tandem isoenzyme genes in Corynebacterium glutamicum and its application in conversion of cane molasses to D‐allulose. Issue 4 (23rd January 2019) - Yang, Jiangang; Tian, Chaoyu; Zhang, Tong; Ren, Chenxi; Zhu, Yueming; Zeng, Yan; Men, Yan; Sun, Yuanxia; Ma, Yanhe
Abstract: D ‐Allulose 3‐epimerase (DAE) has been applied to produceD ‐allulose, a low‐calorie and functional sweetener. In this study, a new DAE from Paenibacillus senegalensis was characterized in Escherichia coli . Furthermore, we presented a tandem isoenzyme gene expression strategy to express multiple DAEs in one cell and construct food‐grade expression systems based on Corynebacterium glutamicum . Seventeen expression cassettes based on three DAE genes from different organisms were constructed. Among all recombinant strains, DAE16 harboring three DAE genes in an expression vector exhibited the highest enzyme activity with 22.7 U/mg. Whole‐cell transformation of DAE16 produced 225 g/LD ‐allulose with a volumetric productivity of 353 g·g −1 ·hr −1 . The catalytic efficiency of strain C‐DAE9 integrating total 11 DAE genes in chromosome was 16.4‐fold higher than strains carrying one DAE. Fed‐batch culture of C‐DAE9 gave enzyme activity of 44, 700 U/L. We also expressed a thermostable invertase in C. glutamicum and obtained enzyme activity of 29 U/mg. Immobilized cells expressing DAE or invertase exhibited 80% of retained activity after 30 cycles of catalytic reactions. Those immobilized cells were coupled to produce 61.2 g/LD ‐allulose from cane molasses in a two‐step reaction process. This study provided an efficient approach for enzyme preparation and allowed access to produceD ‐allulose from other abundant and low‐cost feedstock enriched with sucrose. Abstract : A tandem isoenzyme gene expression strategy has been applied to express multiple D‐allulose 3‐epimerases (DAEs) in one cell and facilitates constructing food‐grade expression systems based on Corynebacterium glutamicum. Abundant raw materials cane molasses have been converted to D‐allulose by one‐pot, two‐step reaction process.